Is open innovation always the best for SMEs? An exploratory analysis at the project level. (23rd April 2020) - Marullo, Cristina; Di Minin, Alberto; De Marco, Chiara; Piccaluga, Andrea
Abstract : Open innovation (OI) projects are increasingly adopted by small‐ and medium‐sized enterprises (SMEs). Yet, undertaking OI is not only a source of opportunities for SMEs as it can, at the same time, present risks. How SMEs manage the balance between the potential benefits and the emerging challenges of OI is still an overlooked topic in the literature. Using evidence gathered through multiple case studies and drawing upon the relational view of the firm, we explore how and why value creation opportunities and different managerial challenges emerge for SMEs pursuing OI projects. We analyze different stages of OI projects in several different contexts of their implementation. Our analysis sheds light on the different nature and dynamics of knowledge involved within OI projects as important boundary conditions affecting successful search paths, learning processes, and the development of appropriability mechanisms. By offering a contextualized view of OI in SMEs, this study also provides insights to business managers on the situational opportunities and constraints of OI, including managerial suggestions on actions to manage tensions within differing OI projects.